The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1994
DOI: 10.1111/j.1365-2648.1994.tb01205.x
|View full text |Cite
|
Sign up to set email alerts
|

The quality of assessment visits in community nursing

Abstract: The aim of this study was the measurement of the quality of assessment visits of community nurses in The Netherlands. Process criteria were derived for the quality of the assessment visits from the quality standards of community nursing care established by Appelman et al. Over a period of 8 weeks, a representative sample of 108 community nurses and 49 community nursing auxiliaries at 47 different locations paid a total number of 433 assessment visits. The nursing activities were recorded for each visit. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2004
2004
2006
2006

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…For example, in the Netherlands Kerkstra and Beemster (1994) reported that there was pressure from health insurance companies for a more structured and objective assessment method for home care. For example, in the Netherlands Kerkstra and Beemster (1994) reported that there was pressure from health insurance companies for a more structured and objective assessment method for home care.…”
Section: Political Influences On Assessment Practicementioning
confidence: 99%
See 1 more Smart Citation
“…For example, in the Netherlands Kerkstra and Beemster (1994) reported that there was pressure from health insurance companies for a more structured and objective assessment method for home care. For example, in the Netherlands Kerkstra and Beemster (1994) reported that there was pressure from health insurance companies for a more structured and objective assessment method for home care.…”
Section: Political Influences On Assessment Practicementioning
confidence: 99%
“…In other parts of the world political and/or organizational control over community nursing assessments can be identified. For example, in the Netherlands Kerkstra and Beemster (1994) reported that there was pressure from health insurance companies for a more structured and objective assessment method for home care. In the USA community nurses are required by various care agencies to complete forms during the assessment process (Armentrout, 1998).…”
Section: Political Influences On Assessment Practicementioning
confidence: 99%